2019
DOI: 10.1002/ijc.32520
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic downregulation of TET3 reduces genome‐wide 5hmC levels and promotes glioblastoma tumorigenesis

Abstract: Loss of 5‐hydroxymethylcytosine (5hmC) has been associated with mutations of the ten–eleven translocation (TET) enzymes in several types of cancer. However, tumors with wild‐type TET genes can also display low 5hmC levels, suggesting that other mechanisms involved in gene regulation might be implicated in the decline of this epigenetic mark. Here we show that DNA hypermethylation and loss of DNA hydroxymethylation, as well as a marked reduction of activating histone marks in the TET3 gene, impair TET3 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 56 publications
(106 reference statements)
2
32
0
1
Order By: Relevance
“…Considering that 5mC and TET2 are both closely related to the regulation of DNA methylation, it might be reasonable to hypothesize that 5mC and TET2 also participate in the etiology of the existence or progression of precancerous lesion. In this study, we found that 5hmC and TET2 expressions were both negatively correlated with the histological classification, and here were several possible explanations to the results in our study: (a) 5hmC and TET2 might prevent the formation or repress the progression of breast precancerous lesion via modulating stemness or other related processes, which still need more in vivo and in vitro experiments to validate; (b) 5hmC and TET2 might also inhibit precancerous lesion development and progression via similar mechanism by which they suppress the cancer progression, for instance, repressing malignant behaviors of cancer cells by mediating multiple oncogenic signaling pathways . However, we did not find a statistically significant correlation between 5mC and histopathological classification, which may be due to the dual role of 5mC in cancer pathogenesis found in other cancers, or a relatively small sample size …”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Considering that 5mC and TET2 are both closely related to the regulation of DNA methylation, it might be reasonable to hypothesize that 5mC and TET2 also participate in the etiology of the existence or progression of precancerous lesion. In this study, we found that 5hmC and TET2 expressions were both negatively correlated with the histological classification, and here were several possible explanations to the results in our study: (a) 5hmC and TET2 might prevent the formation or repress the progression of breast precancerous lesion via modulating stemness or other related processes, which still need more in vivo and in vitro experiments to validate; (b) 5hmC and TET2 might also inhibit precancerous lesion development and progression via similar mechanism by which they suppress the cancer progression, for instance, repressing malignant behaviors of cancer cells by mediating multiple oncogenic signaling pathways . However, we did not find a statistically significant correlation between 5mC and histopathological classification, which may be due to the dual role of 5mC in cancer pathogenesis found in other cancers, or a relatively small sample size …”
Section: Discussionmentioning
confidence: 51%
“…These findings indicate a dual role of 5mC in tumorigenesis. As for 5hmC, a previous study reveals that epigenetically reduction of TET3 expression decreases the 5hmC expression in both tumor tissue and cancer cells, and this process subsequently advocates the tumor progression of glioblastoma in vitro . And another study illustrates that restoring the 5hmC using ascorbate represses the tumor growth of clear‐cell renal cell carcinoma in vitro .…”
Section: Discussionmentioning
confidence: 97%
“…TET protein family are usually considered as tumor suppressors by promoting locus-specific reversal of DNA methylation [ 13 , 28 , 29 ], however, the detailed molecular mechanisms of TET protein family regulating NPC progress are still unclear. In this study, we first examined the mRNA expression levels of TET family genes in NPC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…For example, hm 5 C is distributed at lncRNA loci, involved in long-range chromatin interactions and positively correlated with lncRNA transcription [130]. TET1 is elevated in GBM [85], while TET2 expression is downregulated in glioma [86], and TET3 is epigenetically repressed in glioma [87]. 5-hydroxymethylcytidine in DNA has been recognized as important markers in GBM [131][132][133], however, the direct evidence of hm 5 C modification in RNA has never been explored in GBM (Figure 2, hm 5 C part).…”
Section: Rna Hm 5 C Modification In Gbmmentioning
confidence: 99%